2019
DOI: 10.1186/s12881-019-0913-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of CCR5delta32 in Northeastern Iran

Abstract: Background: A 32-base pair deletion (Δ32) in the open reading frame (ORF) of CC motif chemokine receptor 5 (CCR5) seems to be a protective variant against immune system diseases, especially human immunodeficiency virus type 1 (HIV-1). We aimed to assess the frequency of CCR5Δ32 in the healthy Iranian population. Methods: In this study, 400 normal samples from Khorasan, northeastern Iran, were randomly selected. The frequency of CCR5Δ32 carriers was investigated using PCR analysis. Allele prevalence and the fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
1
3
0
1
Order By: Relevance
“…In the present study, the frequency of the CCR5 Δ 32 allele in healthy Turkmen people was not found. This is consistent with other studies from Iran [ 16 , 17 , 46 , 53 , 54 ] and other countries [ 55 – 62 ]. In contrast to our research, Trecarichi et al have shown a significantly higher frequency of Δ 32 in the healthy control group compared to HIV-positive people.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, the frequency of the CCR5 Δ 32 allele in healthy Turkmen people was not found. This is consistent with other studies from Iran [ 16 , 17 , 46 , 53 , 54 ] and other countries [ 55 – 62 ]. In contrast to our research, Trecarichi et al have shown a significantly higher frequency of Δ 32 in the healthy control group compared to HIV-positive people.…”
Section: Discussionsupporting
confidence: 93%
“…Also, CCR5 Δ 32 is absent in East and Southeast Asian populations, natives of America, Oceania, and sub-Saharan Africa [ 50 ]. In the Iranian people, the frequency of CCR5 Δ 32 is estimated at 1.6%, which varies in different ethnicities living in this country [ 16 , 17 ]. By the end of 2021, 38.4 million HIV-infected individuals worldwide have been detected, with the highest frequency observed in South and West Africa (20.6 million infected) and the lowest in the Middle East and North Africa (18,000 infected) [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severe inflammatory response and corneal damage associated with fungal infections may be due to the overproduction of C–C chemokine, which can activate monocytes and T-cells, leading to a more severe inflammatory response in the cornea. 33 Fungal infection also induces phosphorylation of PI3K/Akt in the corneal tissue of mice with fungal keratitis, which is associated with m6A modification. 34 There are two conclusions to be drawn from the evidence presented here: m6A modification plays a role in the pathogenesis of fungal keratitis, and modulation of m6A methylation may be another approach to the treatment of this disease.…”
Section: The Roles Of M6a Modification In the Individual Complex Eye ...mentioning
confidence: 99%
“…A síndrome da Imunodeficiência Adquirida diagnosticada em decorrência da infecção do vírus HIV é apresentada por diversos fatores e processos tais como período de latência que é quando ocorre a infecção do HIV com o DNA viral no interior das células TCD4+ caracterizada pela baixa atividade transcricional ou nenhuma atividade detectada no SAÚDE PÚBLICA NO BRASIL: UM PANORAMA ATUAL 236 organismo podendo exceder por um longo período até que a replicação viral seja detectável e o sistema imune comprometido (YUKL et al, 2018).Sendo a interação do vírus HIV com os dois correceptores CC, o tipo 5 CCR5 e o tipo 4 CRX4 que provocam uma cascata de eventos bioquímicos devido à esta ligação (HAYASHIDA et al, 2017;WANG et al, 2017) O paciente de Berlim como ficou conhecido o homem morador de Berlim (Alemanha), diagnosticado com HIV-1 durante anos de sua vida, após receber um transplante de medula óssea para tratamento da leucemia mieloide aguda, obteve a remissão do vírus HIV ao qual permaneceu indetectável a replicação viral (SOUZA et al, 2012). Essa remissão do HIV no paciente aconteceu devido uma mutação no correceptor CCR5delta32 genótipo homozigoto, na qual ocorre a deleção dos 32 nucleotídeos do gene CCR5 apresentando uma proteína defeituosa que não é expressa na membrana das células (TAJBAKHSH et al, 2019)Essa condição proporciona resistência ao HIV-1 e retarda a progressão da AIDS nos indivíduos infectados, sendo conhecidos como "controladores de Elite do HIV" que conseguem suprimir o vírus sem tratamento anti retroviral (SALGADO et al, 2018).…”
Section: Diferenças Entre Os Portadores Da Aids E Os Controladores De...unclassified